2021
DOI: 10.1002/lary.29838
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Telemedicine for Diagnosis and Management of Laryngology‐Related Complaints during COVID‐19

Abstract: Objectives/Hypothesis To investigate the concordance in diagnosis and management between initial telemedicine visits and subsequent in‐person visits with laryngoscopy for laryngology‐related complaints during COVID‐19. Study Design Retrospective cohort study. Methods Patients who presented to a tertiary care center with laryngology‐related complaints (voice, swallowing, airway, general throat complaints and others) and completed initial telem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Other authors have reported high diagnostic reliability in patients with various ENT conditions, including otologic conditions, rhinosinusitis, peritonsillar abscess, and nasal fracture 14 . The diagnostic accuracy and effectiveness of empiric therapy provided during TM visits are of particular interest in determining the feasibility of its use in the effective management of patients 14 . A limitation to this type of approach is the need for an adequately trained health care technician to perform diagnostic and minor therapeutic procedures 13 , 15 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Other authors have reported high diagnostic reliability in patients with various ENT conditions, including otologic conditions, rhinosinusitis, peritonsillar abscess, and nasal fracture 14 . The diagnostic accuracy and effectiveness of empiric therapy provided during TM visits are of particular interest in determining the feasibility of its use in the effective management of patients 14 . A limitation to this type of approach is the need for an adequately trained health care technician to perform diagnostic and minor therapeutic procedures 13 , 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Other alternatives described are voice recordings and speech analysis systems for speech pathology, although access to these investigations is still limited 9 , 18 . However, some authors have pointed out that the exclusive use of radiologic investigations for diagnosis is a deviation from the standard of care and may have medicolegal implications 14 . Kwok et al showed that in resource-limited settings and particularly in crisis situations such as the COVID-19 pandemic, simple initial telephone consultation has high concordance with the final treatment plan despite some limitations in diagnostic concordance due to the inability to perform physical examination 17 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations